TINJAUAN LITERATUR TENTANG ANCAMAN CYBERCRIME DAN IMPLEMENTASI KEAMANAN SIBER DI INDUSTRI PERBANKAN - Nasywa Shafa Azzahra; Aron Micael Tambunan, Najwa Nayra Aulia, Arista Binarsih, Tubagus Hedi Saepudin (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Rapid technological development brings significant changes in social, economic and cultural aspects, but also increases the risk of the spread of viruses, piracy and software attacks. Cybercrime, as a cross-border crime, is a serious threat with far-reaching impacts, especially in the banking industry. This research reviews the literature regarding cybercrime threats and the implementation of cyber security in the banking sector, with a focus on threats such as Phishing, Malware, and data leaks that cause theft of sensitive information, financial losses, and reputational damage. Through a literature review of five journals, this research aims to identify the main threats of cybercrime, evaluate bank security measures, and recommend strategies for improving cyber security. Although the evaluation of cybersecurity policies faces obstacles, preventive measures have been taken. Increasing cyber security and cooperation between institutions is very important in facing the threat of cybercrime in the financial sector.